Management of wooden foreign bodies in craniofacial region - Kamaraj Loganathan; James P. Chacko; B.S. Saravanan; Bindu Vaithilingam (Elsevier, 2012)
Even though variety of foreign bodies has been reported in a various locations in the craniofacial region, wooden foreign bodies are uncommon. Appropriate management of wooden foreign bodies is considered essential because of their infectious complications and difficulty in radiographic localization. Even though literature is replete with articles on management of foreign bodies in the craniofacial region, specific management of wooden foreign bodies are rarely reported. The purpose of this article is to report two cases of deeply placed wooden foreign body and a protocol for managing them in the maxillofacial region.